The effects on type 2 diabetes mellitus mouse femoral bone achieved by anti-osteoporosis exercise interventions - Zhang, Miao; Li, Yuexuan; Liu, Lifei; Huang, Mei; Wang, Miao; Zou, Jun (Frontiers in Endocrinology, 2022)
Purpose： Exercise therapy，key regulators of the actions of bone quality, exert anti-hyperglycemic effects in type 2 diabetes mellitus (T2DM) mice. few programs have been reported effective in bone disease of type 2 diabetes mellitus (T2DM). A major unanswered question concerns the potential ability of exercise to improve bone quality in T2DM mice. Methods: Subjects were randomly divided into 6 groups: control (C) group who was fed with a normal diet (n=8); T2DM quiet group who received high-fat diet and quiet (n=8); T2DM puls swimming (S) group who received T2DM and swimming (n=8); T2DM puls resistance (RE) group who received T2DM and resistance exercise (n=8); T2DM puls aerobic (AE) group who received T2DM and medium intensity treadmill exercise(n=8); T2DM puls high-intensity interval training (HIIT) who received T2DM and high intensity variable speed intervention (n=8). The levels of Runt-related Transcription Factor 2 (RUNX2), Osterix (OSX), alkaline phosphatase (ALP), microstructure and morphometry were measured after 8-week exercise intervention. Results: 1) T2DM mice showed that the gene expression of osteogenesis (RUNX2, OSX, and BMP2), the trabecula of BV/TV, TMD and Conn.D, the cortical bone of Ct.Th and TMD the whole bone of BMD and BV/TV, and the mechanical parameters of (maximum load, fracture load, yield stress and elacstic modulus) decreased, the trabecula of BS/BV levels increase, respectively (all p<0.05). 2) The AE and HIIT were able to upregulate the Osterix，RUNX2 and ALP expression in T2DM mice, thus improving the normalization of Osteogenic differentiation (all p<0.05). 3) In the microstructure of bone trabeculae, HIIT increased the value of Tb.N, BV/TV, TMD, Conn.D, DA and reduced the value of Tb.Sp compared with the T2DM+NE group(all p<0.05). AE increased the value of Tb.N and reduced the value of Tb.Sp compared to the T2DM group mice (all p<0.05). RE and S showed significantly worse compared to the HIIT and AE group (all p<0.05). 4) In the microstructure of cortical bone, AE significantly increased the value of Ct.Th and BMD when compared with the other three exercise intervention groups (all p<0.05). But HIIT reduced the value of BV/TV and Ct.Th